PENGARUH PENDAPATAN ASLI DAERAH DAN DANA BAGI HASIL TERHADAP PERTUMBUHAN EKONOMI MELALUI BELANJA LANGSUNG DI KABUPATEN ACEH TAMIANG - NURAINI; Yani Rizal; Iskandar Iskandar (Fakultas Ekonomi Universitas Samudra, 2023)
Regional economic growth can be calculated and predicted through the magnitude of the figures listed in the gross regional domestic product (GRDP) table. GRDP is defined as the totality of the accumulation of goods and services produced by a region in its economic cycle. GRDP at constant prices is used as a reference in calculating the economic growth rate of a region. To analyze the direct effect of regional original income and revenue sharing on direct spending through economic growth and to analyze the indirect effect on regional original income and revenue sharing on the rate of economic growth.